Effects of salt particle size and sample preparation on results of mixer-efficiency testing - Groesbeck, C.N.; Goodband, Robert D.; Tokach, Michael D.; Nelssen, Jim L.; DeRouchey, Joel M.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
Two experiments were conducted to evaluate the effects of using salt with different particle sizes and of using different samplepreparation methods on mixer-efficiency testing (time required to achieve a coefficient of variation (CV) of 10% or less among 10 feed samples). A 3000-lb capacity horizontal ribbon mixer was used to mix batches of feed. Ten samples were collected at eight times during mixing (0.0, 0.5, 1.0, 2.0, 3.5, 5.5, 8.0, and 10.5 min) after all ingredients were added from pre-determined locations in the mixer. Coefficient of variation was used to measure mixer efficiency by analysis for chloride concentration in each sample with Quantab® chloride titrators. In Exp. 1, four 3000-lb batches of feed were prepared, two with 440- micron salt and two with 730-micron salt. Samples were analyzed as collected (unground; approximately 700 microns) or were ground with a coffee grinder (ground; approximately 400 microns). A salt particle size × sample preparation × mixing time interaction (P<0.001) was observed, but a CV of 10% or less was never achieved, indicating inadequate mixing. In Exp. 2, all samples were collected from 2000-lb batches of feed made in the 3000-lb-capacity mixer. Four different salt particle sizes (440, 730, 1999, and 3000 micron) were used, and each set of samples collected was also analyzed as unground or ground. A salt particle size × sample preparation × mixing time interaction (P<0.04) was observed. As salt particle size decreased and mixing time increased, there was a decrease in CV. Grinding samples before analysis decreased CV, compared with that of the unground samples, but to a greater extent with coarse salt than with fine salt. The batch mixed with 440-micron salt and the batch mixed with 730-micron salt (ground) reached a CV of less than 10%, indicating a uniform mixture. No other treatments reached a CV of 10% or less. When the mixer was filled to the rated capacity we were unable to achieve an acceptable CV for mixer efficiency; therefore, it is important to test mixers at various fill levels. Our study also showed that it is important to use a fine mixing salt when testing mixers for mixer efficiency.
Keywords: Swine; Mixer efficiency; Particle size; Pigs; Salt